På spaning efter den populärkulturelle Bergman: Om att vända på bilden av en filmskapare - Burman, Christo (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2010)
Ingmar Bergman’s name is virtually synonymous with intellectual European films and high culture but lately scholars have been trying to show that Bergman worked in a veriety of fields, including popular culture, and that his work often was commercial, popular and more easily accessible than his auteur image would suggest. This article explores some of the soap commercials that Bergman made in the early 1950s, which still remain a little known part of his oeuvre. The focus also lies on the publication of Bergman’s scripts as serial "film novels" in the weekly women’s magazine Allers Familjejournal (1959-1967) and on the transformation of the image of Bergman by his popular later works Scenes from a Marriage (1973) and Fanny and Alexander (1982) and through famous images that reappear throughout the spectrum of popular culture, most notably the image of Death from The Seventh Seal (1957).